The Relationship Between Training Environment and Training Effectiveness of PNB, CFA Student - Asraf , Abdul Rahman (2012)
This study attempt to evaluate the training effectiveness provided by external trainer organised by PNB Investment Institute. This study also identify the influencing factors that affect the training effectiveness, that is training environment. Adopted Questionnaires were used for data Collection. Out of 33 participants, 32 respondents returned their questionnaire, making the responses rate of 97 percent. Data was processed and analyse using SPSS. Appropriate data analysis technique were used, both for descriptive and inferential analysis. Findings show that respondents perceived that training environment provided by PNB Investment Institute are good especially on their ability in task involvement. Findings also revealed that training environment is significantly associated and influenced the training effectiveness. Suggestion for future research was made at the section of this study